Optimization of total RNA extraction from human urinary sediment - Saseevan, S.; Magana-Arachchi, D.N.; Rajapakse, S. (Postgraduate Institute of Science Research Congress, Sri Lanka, 2021)
Urine is the best choice to identify biomarkers for metabolic and renal disorders because it is readily available, and samples can be obtained non-invasively from patients. However, RNA isolation from voided urine is challenging due to the presence of RNases and cell scarcity. This study aims to optimize a protocol for RNA extraction from urine samples in gene expression studies. Twenty urine samples were collected from healthy controls (HC) (n = 11; 49 ± 5 years) and chronic kidney disease (CKD) patients (n = 9; 62 ± 3 years) and were centrifuged at 3,000 g for 30 min at 4 °C. Then, 500 μL of the lysis buffer was added to the pellet, vortexed and kept on ice for 5 min. Next, 100 μL of sodium acetate (pH = 4.0) and 500 μL of water-saturated phenol were added and mixed well. After that, 200 μL of chloroform: isoamyl alcohol (49:1) was added, vortexed and centrifuged. An equal volume of cold isopropanol was added to the aqueous phase and incubated at -20 °C for 1 h to precipitate RNA. The pellet was washed with 75% ethanol, air dried, and resuspended with 12 μL nuclease-free water. Finally, the RNA was quantified and reverse transcribed into cDNA to be used in RT-qPCR. Mean urine volume was 82.5 ± 41.9 mL. Serum creatinine and estimated glomerular filtration rate of CKD patients were 3.0 ± 0.2 mg dL-1 and 19.2 ± 4.8 mL min-1 1.73 m-2, respectively. The total yield of RNA from CKD and HC samples were 873 ± 523 ng and 735 ± 291 ng, respectively, and a statistically significant difference was not observed between the two study groups (p > 0.05). The β2 microglobulin gene could be successfully amplified using samples even with a low cDNA concentration (0.625 ng). This modified phenol-chloroform based urinary RNA isolation method is less expensive, does not require RNA clean-up kits and provides a higher yield of RNA with less inhibition which is sufficient for downstream applications than column-based techniques.
Keywords: Chronic kidney disease; RNA isolation; Urinary sediment